Booster immunization with a hexavalent diphtheria, tetanus, acellular pertussis, hepatitis B, inactivated poliovirus vaccine and Haemophilus influenzae type b conjugate combination vaccine in the second year of life: Safety, immunogenicity and persistence of antibody responses - Heininger, U.; Sänger, R.; Jacquet, J.-M.; Schuerman, L. (Vaccine, 2007)
The immunogenicity and reactogenicity of booster vaccination with GSK Biologicals’ hexavalent DTPa-HBV-IPV/Hib vaccine was assessed in toddlers aged 12–18 months previously primed with the same combination ( N = 341), or with DTPa-IPV/Hib and HBV administered separately ( N = 102; Trials 217744/059 and 217744/096). Antibody persistence at age 4–6 years was also assessed in children who had received a 4th consecutive dose of DTPa-HBV-IPV/Hib vaccine or separate DTPa-IPV/Hib and HBV vaccines in this study and in another study conducted under similar conditions in Germany. Prior to booster vaccination in the second year of life, antibody concentrations and seroprotection rates were similar irrespective of the primary vaccine used. One month after boosting with DTPa-HBV-IPV/Hib, substantial antibody increases were observed against all vaccine antigens indicative of previous immune priming. Seropositivity and booster response rates against all antigens were 97.4–100%. Reactogenicity following booster vaccination with DTPa-HBV-IPV/Hib was similar regardless of the primary regimen used. Three to four years after administration of the 4th DTPa-HBV-IPV/Hib dose, >90% vaccinees had persistent protective antibody concentrations against diphtheria, hepatitis B, Hib and the three poliovirus types. Anti-tetanus antibody concentrations were ≥0.1 IU/ml in 76.4% subjects and seropositivity for pertussis antibodies ranged from 34.5% for PT to 98.9% for FHA. In conclusion, the combined hexavalent DTPa-HBV-IPV/Hib vaccine is immunogenic and safe when used for boosting in the second year of life, regardless of the primary vaccine used, and offers sustained protection during early childhood and beyond.